2014
DOI: 10.1007/s00277-014-2131-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 and 9 genetic polymorphisms and the susceptibility to B cell Non-Hodgkin Lymphoma in Egypt

Abstract: Non-Hodgkin lymphomas (NHL) entail considerable heterogeneity regarding their morphology, clinical course, etiological factors, or response to therapy. Increased incidence of NHL in immunocompromised individuals and after autoimmune diseases suggests that infections and immune dysregulation could play a role in the susceptibility to NHL. Accordingly, genetic variation in Toll-like receptor (TLR) genes might be considered as molecular risk factors for NHL. The aim of the current study was to investigate the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several studies have shown that TLR-9 engagement on cluster of differentiation 4-positive (CD4 + ) T cells can enhance their survival and therefore potentiate anticancer responses by prolonging T-cell activity 14. Previous studies have indicated that TLR-9 polymorphisms may be associated with the risk of developing several types of cancers, including bladder cancer,15 prostate cancer,1618 acute lymphoblastic leukemia,19 hepatocellular carcinoma,20 gastric cancer,21,22 cervical cancer,23 Hodgkin’s lymphoma,24 breast cancer,25 Burkitt’s lymphoma,26 non-Hodgkin’s lymphoma,27 endometrial cancer,28 esophageal cancer,23 and lymphoma 24,27,29. However, the results are inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that TLR-9 engagement on cluster of differentiation 4-positive (CD4 + ) T cells can enhance their survival and therefore potentiate anticancer responses by prolonging T-cell activity 14. Previous studies have indicated that TLR-9 polymorphisms may be associated with the risk of developing several types of cancers, including bladder cancer,15 prostate cancer,1618 acute lymphoblastic leukemia,19 hepatocellular carcinoma,20 gastric cancer,21,22 cervical cancer,23 Hodgkin’s lymphoma,24 breast cancer,25 Burkitt’s lymphoma,26 non-Hodgkin’s lymphoma,27 endometrial cancer,28 esophageal cancer,23 and lymphoma 24,27,29. However, the results are inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The variant heterozygous genotype of the TLR9 rs5743836 SNP conferred almost a fourfold increased risk of B-cell Non-Hodgkin lymphomas (B-NHL) in patients from Egypt (OR = 3.93, 95% CI = 2.16–7.14) [ 22 ]. This observation was supported neither by our study nor by the meta-analysis that included 25,685 subjects that suggested that the TLR9 rs352140 and rs5743836 SNPs were associated with a decreased risk of development of breast and digestive system cancers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small study that included 62 adult patients with AML from Poland showed that TLR9 rs5743836 and rs187084 gene polymorphisms were associated with predisposition to the disease [ 16 ]. TLR9 rs5743836, polymorphism may represent a molecular risk factor for B-cell Non-Hodgkin lymphomas (B-NHL) among Egyptian subjects [ 22 ]. No significant association between rs2066807 and rs187084 SNPs of the TLR9 genes and the risk of chronic lymphocytic leukemia (CLL) in the Egyptian population was reported previously [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] This generated a 135 bp fragment. The amplified material was digested by BstNI enzyme (Fermentas-Lithuania).…”
Section: Methodsmentioning
confidence: 99%